TO DEVELOP SKILLS OF SPEAKING IN B1 LEVEL STUDENTS. - Malikaxon Sharofiddinova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  aims  to  explore  effective  methods  for  developing speaking skills in B1 level students, focusing on the importance of communicative competence.  Through  a  literature  analysis,  various  strategies  will  be  examined  to identify key elements that contribute to successful language acquisition at this level. The  methods  section  will  outline  practical  approaches  for  educators,  incorporating interactive activities and motivation techniques. The results section will present the outcomes of applying these methods, followed by a discussion that delves into the implications of the  findings. Finally,  the article  will conclude  with suggestions  for further research and practical recommendations for teachers.